The synthesis of iron nanoparticles in the hydro-alcoholic solution of ferric chloride - Аbdullin, Kh.А.; Gabdullin, М.Т.; Ramazanov, Т.S.; Batryshev, D.G.; Ismailov, D.V.; Schur, D.V.; Kerimbekov, D.S. (Recent Contributions to Physics, 2015)
In this work the method of nano- and microparticles synthesis in plasma of arc discharge in the liquid phase is considered. Nano- and microparticles of various chemical compositions can be synthesized under proposed method. The mechanism and scheme of combination of the chemical composition of electrode material and liquid medium were suggested. The advantages of proposed method are simplicity of the method, no bulky control systems and electrical power, absence of strongly heated elements in the plasma chemical process, no need to use of harmful gases and reactor cooling system, high temperature of the arc (above 4000 K) and high speed cooling vaporized product, synthesis of nanostructured materials without vacuumization procedure. On the basis of this method in the hydro-alcoholic solution of ferric chloride the samples of iron nano- and microparticles were obtained. The influence of magnetic field on a synthesis process is studied. The different iron nanoparticle fractions were obtained using additional magnetic field in the area of plasma chemical reaction. The obtained nanoparticles at Н = 0 have sizes 1¸100 nm and at Н≠0 have 25¸250 nm. The chemical composition analysis, morphology and geometric size estimation of synthesized samples were carried out on a scanning and transmission electron microscopes.